Preanthesis biomass accumulation of plant and plant organs defines yield components in wheat - Xie, Quan; Mayes, Sean; Sparkes, Debbie L. (Elsevier, 2016)
The preanthesis period in wheat is critical for growth of plant organs including leaves, stems, spikes and roots. However, the roles of the preanthesis biomass accumulation of plant and plant organs in yield determination are only partially elucidated, and the underlying genetic basis remains largely unknown. This study aimed to understand the physiological and genetic relationships between preanthesis biomass accumulation and yield determination. In a mapping population of bread wheat (Triticum aestivum ‘Forno’) and its relative spelt (Triticum spelta ‘Oberkulmer’) contrasting for biomass, the dry weight of above-ground whole shoots and different organs, and leaf area, were analysed at GS39 (full flag leaf emergence) and anthesis. Yield components (thousand grain weight, grains per spike, final shoot biomass and grain weight per spike) and plant height were measured at maturity, followed by identification of quantitative trait loci (QTL) for all above traits. Field experiments were carried out in UK in 2011–2012 and 2012–2013 seasons, each using a randomised complete block design with three replicates. The results showed that there was a significant variation in biomass and its partitioning to organs at different stages. Consistent with the previous findings, stem water soluble carbohydrates and spike dry weight at anthesis contributed to thousand grain weight and grains per spike, respectively. In addition, this study revealed many other traits positively associated with one or more yield components, including biomass and leaf area at GS39, leaf and structural stem growth as well as whole shoot biomass at anthesis, and higher dry matter accumulation and crop (and spike) growth rates between the two stages. Increasing shoot biomass by removing other tillers at GS39 led to higher grain number and grain weight per spike. These results indicate the importance of the preanthesis growth of plant and plant organs for yield determination. Plant height was only weakly correlated with final biomass at maturity so it is possible to produce high-biomass genotypes without increasing plant height. Genetic analysis revealed 193 QTL associated with biomass and biomass-related traits. Frequent QTL coincidences between biomass and yield traits were observed, mainly on chromosomes 2B, 3A, 4A, 4B, 5A, 6A and 7B, indicating pleiotropy or tight gene linkages, consistent with their phenotypic associations. The preanthesis biomass traits associated with yield components and the underlying QTL, would facilitate the trait-based physiological and molecular breeding in wheat.